2012
DOI: 10.1016/j.apgeochem.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Tracing interactions between natural argillites and hyper-alkaline fluids from engineered cement paste and concrete: Chemical and isotopic monitoring of a 15-years old deep-disposal analogue

Abstract: International audienceSamples of Toarcian argillite were collected both next to and far from a CEM II cement paste and a CEM II concrete, within the specific context of a 15-a old borehole located in the Tournemire Experimental Platform (Aveyron, France). The objectives were evaluation of the mineralogical and geochemical changes of the claystone at the contact with the cementitious materials and determination of the spatial extent of the interactions. The approach includes the examination of the mineralogic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Similar Mg-rich solid phases have been observed previously as minor components in high pH clay alteration experiments/analogues. For example, saponite was recognised as an alteration product of bentonite by Cuevas (2004), secondary Mg-enriched mineral phases have been observed at the Tournemire analogue site (Tinseau et al, 2006;Techer et al, 2012) and palygorskite was identified as an Mg-rich alteration product of bentonite by high pH groundwaters in the Troodos natural analogue site (Alexander et al, 2012). The formation of these phases at these high pH conditions is not unexpected as they are commonly associated with alkaline, saline lake environments (Yeniyol, 2007(Yeniyol, , 2012Hojati et al, 2010;Akbulut and Kadir, 2003) where they form from post-sedimentary alteration of soils and rocks in high pH fluids in the presence of dolomitic material (Derkowski et al, 2013;Xie et al, 2013;Schwarzenbach et al, 2013;Birsoy, 2002).…”
Section: Mg-silicate Formationmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar Mg-rich solid phases have been observed previously as minor components in high pH clay alteration experiments/analogues. For example, saponite was recognised as an alteration product of bentonite by Cuevas (2004), secondary Mg-enriched mineral phases have been observed at the Tournemire analogue site (Tinseau et al, 2006;Techer et al, 2012) and palygorskite was identified as an Mg-rich alteration product of bentonite by high pH groundwaters in the Troodos natural analogue site (Alexander et al, 2012). The formation of these phases at these high pH conditions is not unexpected as they are commonly associated with alkaline, saline lake environments (Yeniyol, 2007(Yeniyol, , 2012Hojati et al, 2010;Akbulut and Kadir, 2003) where they form from post-sedimentary alteration of soils and rocks in high pH fluids in the presence of dolomitic material (Derkowski et al, 2013;Xie et al, 2013;Schwarzenbach et al, 2013;Birsoy, 2002).…”
Section: Mg-silicate Formationmentioning
confidence: 98%
“…Whereas anthropogenic analogue sites (e.g. the Tournemire Tunnel; Tinseau et al, 2006;Techer et al, 2012) bridge the gap between laboratory experiments and natural analogues. A review of many such sites representing timescales of alteration from $30 years to >1 million years is provided by Savage (2011).…”
Section: Introductionmentioning
confidence: 99%
“…The bluish phase at the cement paste/argillite interface has been characterised as C-S-H in a previous TEM and SEM study [42]. The first observations by SEM of the separation surface showed the occurrence of a honeycomb structure pierced by prismatic minerals (Fig.…”
Section: Si-phase Precipitation Around the Interfacementioning
confidence: 99%
“…This may lead to mineralogical alteration in the barrier system which in turn is expected to locally influence properties like porosity/permeability, swelling pressure or specific retention properties in case of concrete in contact with claystone or compacted bentonite. Laboratory experiments (Adler 2001;Adler et al 2001;Dauzeres et al 2010) and in situ experiments (Read et al 2001;Tinseau et al 2006;Gaboreau et al 2011Gaboreau et al , 2012Techer et al 2012;Jenni et al 2014) demonstrate alteration of both cement paste and claystone adjacent to interfaces. An increase in porosity in the cement paste close to the interface, and clogging in the claystone adjacent to it are commonly predicted by reactive transport modelling (De Windt et al 2008;Marty et al 2009;Kosakowski and Berner 2013;Bradbury et al 2014).…”
Section: Introductionmentioning
confidence: 99%